PENGARUH PROMOSI DAN KESADARAN MEREK TERHADAP MINAT BELI PADA KEDAI KOPI KALA SENJA KOPI GALUH MAS KARAWANG - Andryan Lukman Zuchri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine and explain the level of Buying Interest at Kala Senja Kopi coffeeshop based on, Promotion and Brand Awareness at Kala Senja Kopi coffeeshop. This research was conducted through a statistical technique approach using SPSS 16, data collection using the incidental sampling technique on 314 respondents with research subjects are customers of Kala Senja Kopi coffeeshop. Prior to the Hypothesis test, this study conducted a data validity test. The data analysis technique used is the scale range analysis technique and path analysis The results of this study reveal that the Promotion of Kala Senja Kopi coffeeshop is in the agreed criteria, that means the Promotion of Kala Senja Kopi coffeeshop are acceptable by consumers. Furthermore, Brand Awareness of Kala Senja Kopi coffeeshop is on agreed criteria, meaning that the Brand Awareness of Kala Senja Kopi coffeeshop could be acceptable by consumers. Then, the Buying Interest of Kala Senja Kopi coffeeshop is on the agreed criteria, that means the Buying Interest of Limasan Cafe are acceptable by consumers. There is a very strong and unidirectional positive correlation between Promotion and Brand Awareness. Partially Promotion had a positive and significant effect on Buying Interest. while brand Awareness also had a positive and significant effect on Buying Interest. The Promotion and Brand Awareness had a positive and significant effect on Buying Interest of Kala Senja Kopi coffeeshop.